(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2021)
Water is available for something like the world’s public’s energy security, with agribusiness accounted for 70% of river use. Leaks in transit and land management, while also suitable processing practices, are the leading causes of water losses and vegetable production. Irrigation for agriculture is the world’s largest user of freshwater, arguing for the widespread application use of data to improve plant health, reduce energy use, and calibrate water usage Even if the Digital revolution (IoT) and also other telecommunication technologies seem like a natural match for smart - grid components, its viability must be included in real-world circumstances via the use of on site pilots. In addition, Home automation software testing games should be adaptable to a wide range of crops, growing conditions, and countries. SWAMP is a project that develops and tests IoT-based smart energy management methods and technologies for precision farming in Europe, Belgium, and Latin America. We go through the project’s SWAMP viewpoint, townscape, crew members, and statistics ways to do things. In this article.